Supervision and Collection of Data about Client - Stendstrom, Nills; Zimmerling-Svan, Barbo; Balldin, Tryggve; Barniškytė, Edita (Socialinė teorija, empirija, politika ir praktika, 2001)
The need for knowledge-based social work is being widely discussed internationally. The Department of Social Work at Stockholm University has taken part in a pilot project in Lithuania, the aim of which is to develop community-based and knowledge-based social work. An educational and training programme has been adopted for this purpose. An important part of this effort is the implementation of a computerised case management system backed by advisory supervision at 14 social service centres throughout Lithuania. The objective of the computerised case management system is to enable social service centres to simply and effectively gather key information about clients, activities and treatment procedures. The objective of the advisory supervision programme is to implement new methods,including a psychosocial approach to relating to clients. The purpose of both programmes is to strengthen the development of the social service centres. The strategy is to analyse the empirical material generated by the computerised case management system. This analysis makes it possible to evaluate and monitor the client population, as well as the procedures employed and the results achieved by the treatment centres. Thus, the computerised case management system enables the staffs of the social service centres to be more aware of what their work entails. This heightened awareness then forms the basis for advisory supervision. The integration of the computerised case management system with advisory supervision is a powerful tool for broadening the interface between research and practice in social work, thereby making social work more securely knowledge-based.